Regulatory T Cells and Type 1 Regulatory T Cells as Immuno-Cell Therapy in Type 1 Diabetes - Sameir, Mohammed; Soleimanifar, Narjes; Selman, NA; Assadiasl, Sara; Sadr, Maryam; Mojtahedi, Hanieh; Mohammed, Ali Jaafar; Nicknam, Mohammad Hossein (Hammurabi Journal of Medical Sciences, 2024)
Type 1 diabetes is caused by the immune system attacking and destroying pancreatic cells, leading to a complete lack of insulin throughout the rest of a person's life. For about 100 years, insulin replacement has been the primary treatment for the majority of people with this condition. Advancements in technology and our knowledge of β cell growth, glucose metabolism, and the immunological pathophysiology of the illness have resulted in the creation of new and effective treatment and preventative strategies. Immunotherapy has undergone a significant transformation, leading to the development of medicines that specifically target immunological mechanisms related to tolerance in the islets. These medicines have the potential to prevent or reverse this disease without the adverse consequences associated with prior techniques that compromised the overall immune system. Cell-based therapies provide potential alternatives to the lifetime administration of insulin in individuals with type 1 diabetes (T1D). Distinct cellular populations are essential in mitigating detrimental immune responses that erroneously embark on an assault on the body's own tissues, paving the way for peripheral tolerance to be established. Natural regulatory T cells (Tregs) are a part of these categories, also in-vitro created Treg cells, and type 1 regulatory T (Tr1) tissues that secrete IL-10. This review specifically examines the roles of regulatory T cells and type 1 regulatory T cells in the field of immunotherapy for type 1 diabetes.